การใช้กากตะกอนส่วนเกินจากระบบบำบัดน้ำเสียแบบแอกติเวเต็ดสลัดจ์ และกากขี้แป้งของโรงงานน้ำยางข้นมาทำเป็นปุ๋ยหมักอัดเม็ด - Faculty of Environmental Management (Environmental Management) (มหาวิทยาลัยสงขลานครินทร์, 2023)
This research study is about using industrial waste from latex rubber industry in southern Thailand for producing pellet organic fertilizer. Industrial wastes applied in this study are sludge from wastewater treatment plant and rubber latex lutoid. In the primary stage, the fertilizer gave C/N ration was very low, high moisture content and fine material, which affected to the slow mechanisam. But after 45 days, the product could reach the Thai organic fertilizer standard according to chemical parameters; N, P, K and heavy metal. However, it was found out that the organic fertilizer from those industrial wastes contained high concentration of Zn, between 0.40 - 5.23 percent by dry weight. Meanwhile, the remaining Zn in the marigold, after 35 days applying as fertilizer to plant 1.5 months old marigold.